A Method for Assessing the Lake Trophic Status Using Hyperspectral Reflectance (400–900 nm) Measured Above Water - Nguyen Thi Thu Ha; Pham Quang Vinh; Nguyen Thien Phuong Thao; Pham Ha Linh; Michael Parsons; Nguyen Van Manh (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
The effective monitoring of eutrophication in inland water bodies is crucial for environmental management and pollution prevention. This study conducts a comprehensive analysis of in situ hyperspectral reflectance data (400–900 nm) and the trophic state index (TSI) obtained from 365 points across ten lakes and reservoirs in Northern Vietnam to propose a trophic classification based on water reflectance spectra features and a TSI estimation model for diagnosis and assessment of lake trophic status. By analyzing the quantity of reflectance peaks and their heights, our study identifies three distinct water reflectance spectra classes corresponding to three trophic levels: mesotrophic to lightly eutrophic, highly eutrophic, and hypertrophic. This classification enables the quick identification of trophic levels directly at the in situ radiometric measurement sites. Our study demonstrates that a logarithmic function of the band ratio, ${R_{rs}}( {715} )/{R_{rs}}( {560} )$ , is robust for estimating TSI ( ${{{\bm{R}}}^2}$ = 0.85 and 0.94; root-mean-square error = 5.0 and 3.7 in calibration and validation, respectively), particularly in algal-dominated waters. These findings represent a practical application of hyperspectral remote sensing for effective eutrophication management. They also highlight the potential use of multispectral optical imagery for monitoring eutrophication in tropical regions.